Mathematical Model of a Levitation System - González C., Alexander (2007)
This paper contains a synthesis to model an electromagnetic levitation system using a direct evaluation method of electromagnetic and electromotive forces, taking the Maxwell equations that relate electric and magnetic fields. The aim of this work is to contribute to researches focussed on developing and optimising mechanisms to provide solutions for applications where mechanical friction must be reduced or eliminated. A prototype is also presented; it will support experimental requirements for curses on automatic control and physical experimentation principles as well as models related with electrostatics and magnetodynamics.